Passiflora foetida L. FLAVONOIDS - Mohammad, Azreen (Universiti Sains Malaysia, 2017)
Flavonoids, aluminium chloride, Passijlora foetida L. Passijlora foetida L. or passion flower is a fast growing spreading vine located near hamlets, top thorny shrubs and human settlements riverbeds. This plant medicinal purpose has been widely purported in countries such as India, Vietnam, Bangladesh, Thailand and Nigeria. In tandem to this, plant medicinal uses are strongly associated with its phytoconstituents content. Thus scientific studies are needed to harness exploitation and outsourcing with well taxonomied plant. One widely known phytoconstituents is the flavonoids. Per se. flavonoids have received a lot of attention in many plant research purposes especially in outsourcing for therapeutic phytoconstituents. Hence this study was carried out to quantify the total flavonoids content in geochemical localized Passiflorafoetida L. leaves and stems extract outsourced form two different GPS location within the state of Kelantan. Chemical characterizations are essential to validate the pharmaceutical use of the plant raw materials. Hence the objective of this work was to optimize a UV/Vis spectrophotometrically method, based on flavonoid-aluminum chloride (AlCh) complexation to determine the total flavonoid content (TFC) in leaves and stems extract of Passijlora foetida L. There is significance different of total flavonoids content in leaves extract between Kampung Kenali and Kampung Pulau Pasir. Flavonoids content in stems extract are suggestively influenced by soil-type and water distribution into the stems structure. The quantification differences can be a bench mark for the optimization of Passijlora foetida L extract.